A Study of Stand-Alone Photovoltaic System Sizing Optimization Using Black Widow Optimization Algorithm - Abdul Jalil, Muhamad Hariz; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2024)
Optimization of SAPV systems is important to ensure cost effectiveness of the system assembly component combination which includes mainly photovoltaic panels, batteries, charge controllers and inverters. This work is aimed as a means of digitally optimizing the configuration of a stand-alone photovoltaic system by using a meta-heuristic approach through the application of a black widow optimization algorithm. The use of MATLAB software as a platform to compile algorithms of Iterative Sizing Algorithm (ISA) and Black Widow Optimization Algorithm (BWO) enables the production of minimal levelized cost of electricity at a fast rate without the need for manual individual component compatibility calculations.